Raspberries 2013
DOI: 10.1079/9781845937911.0021
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development.

Abstract: This chapter focuses on the root, cane and fruit morphology, physiology and growth and development of raspberries. The impact of various climatic factors on the physiology of raspberries are discussed and the medicinal uses and health benefits derived from raspberries are pointed out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…2018) in the current study. In late summer planting systems, raspberry starts acclimating shortly after planting (Durner, 2013;Funt and Hall, 2013), and plant growth primarily occurs the following growing season (Apr. to Sept. 2018 in this study).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…2018) in the current study. In late summer planting systems, raspberry starts acclimating shortly after planting (Durner, 2013;Funt and Hall, 2013), and plant growth primarily occurs the following growing season (Apr. to Sept. 2018 in this study).…”
Section: Discussionmentioning
confidence: 84%
“…Winter injury among plants grown with PE mulch may be a contributing factor to the observed delay in fruit production and the lack of a yield effect observed in this study. Sønsteby and Heide (2014) reported that 'Glen Ample' raspberry (floricane-fruiting) had 71% budbreak after storage at 10°C for 1175 h. Funt and Hall (2013) described that floricane-fruiting raspberries grown across the world require 800 to 1600 chilling hours with a base temperature of 7.2°C. From 1 Oct. to 31 Dec. 2018, plants in this study accumulated 1077 chilling hours (assuming a base temperature of 7.2°C) (WSU AgWeatherNet, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As framboeseiras são plantas perenes e de porte arbustivo, possuem vida relativamente longa, com plantios comerciais ou mesmo plantas em jardins produzindo frutos por até 20 anos, dependendo da localização e das características do solo (Funt, 2013). Possui sistema radicular fasciculado que é considerado a porção perene da planta.…”
Section: Caracterização Da Planta De Framboeseiraunclassified
“…A maior parte das raízes apresenta espessura de 3 a 4 milímetros, mas a podem chegar a 20 mm de espessura quando próximas ao colo da planta. Cerca de 70% das raízes estão distribuídas a profundidade de 25 a 30 centímetros, ainda que a framboeseira busque fontes de água na maioria das vezes na porção de até 60 cm, as raízes podem chegar a 180 cm de profundidade no solo (Oliveira et al, 2007;Funt, 2013). O sistema caulinar das framboesas é composto pelas hastes, também chamadas canas, que apresentam forma cilíndrica e podem apresentar acúleos e pelos ou serem completamente lisas, além de possuírem normalmente uma gema axilar por nó (Tezotto-Uliana e Kluge, 2013).…”
Section: Caracterização Da Planta De Framboeseiraunclassified
See 1 more Smart Citation